Research Article Investigating the Incidence and Management of Postoperative Adhesions in Abdominal Surgery - Muhammad Kalim, Akbar Hussain, Tanvir Ahmad Bhatti, Kamran Ali, M Siddique Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: It is common after surgical procedures, specific to abdominal surgery, to developadhesions. Such formations areextremely indispensible to continued pain, reoccurring pain, andmultifaceted future abdominal procedures. Some patients may be asymptomatic, while patients maydevelop symptoms that are disturbing, and may hinder activities of daily living. In order to improve the treatment given to patients, it is important to assess the occurrence and management ofpostoperative complications